RXLR Effector AVR2 Up-Regulates a Brassinosteroid-Responsive bHLH Transcription Factor to Suppress Immunity. Issue 1 (7th March 2017) - Turnbull, Dionne; Yang, Lina; Naqvi, Shaista; Breen, Susan; Welsh, Lydia; Stephens, Jennifer; Morris, Jenny; Boevink, Petra C.; Hedley, Pete E.; Zhan, Jiasui; Birch, Paul R. J.; Gilroy, Eleanor M.
Abstract : PiAVR2 exploits cross talk between BR signaling and innate immunity in Solanum species, via NbCHL1, representing a novel, indirect mode of innate immune suppression by a filamentous pathogen effector. Abstract: An emerging area in plant research focuses on antagonism between regulatory systems governing growth and immunity. Such cross talk represents a point of vulnerability for pathogens to exploit. AVR2, an RXLR effector secreted by the potato blight pathogen Phytophthora infestans, interacts with potato BSL1, a putative phosphatase implicated in growth-promoting brassinosteroid (BR ) hormone signaling. Transgenic potato ( Solanum tuberosum ) plants expressing the effector exhibit transcriptional and phenotypic hallmarks of overactive BR signaling and show enhanced susceptibility to P. infestans . Microarray analysis was used to identify a set of BR -responsive marker genes in potato, all of which are constitutively expressed to BR -induced levels in AVR2 transgenic lines. One of these genes was a bHLH transcription factor, designated StCHL1, homologous to AtCIB1 and AtHBI1, which are known to facilitate antagonism between BR and immune responses. Transient expression of either AVR2 or CHL1 enhanced leaf colonization by P. infestans and compromised immune cell death activated by perception of the elicitin Infestin1 (INF1). Knockdown of CHL1 transcript using Virus-Induced Gene Silencing (VIGS) reduced colonization of P. infestans on Nicotiana benthamiana . Moreover, the ability of AVR2 to suppress INF1-triggered cell death was attenuated in NbCHL1 -silenced plants, indicating that NbCHL1 was important for this effector activity. Thus, AVR2 exploits cross talk between BR signaling and innate immunity in Solanum species, representing a novel, indirect mode of innate immune suppression by a filamentous pathogen effector.